2021
DOI: 10.3390/rs13040638
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ionospheric Response to June 2009 Sarychev Peak Volcano Eruption

Abstract: Global Navigation Satellite Systems have been extensively used to investigate the ionosphere response to various natural and man-made phenomena for the last three decades. However, ionospheric reaction to volcano eruptions is still insufficiently studied and understood. In this work we analyzed the ionospheric response to the 11–16 June 2009 VEI class 4 Sarychev Peak volcano eruption by using surrounding Russian and Japanese GPS networks. Prominent covolcanictotal electron content (TEC)ionospheric disturbances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…These periodicities also agree with the atmospheric oscillations found by Kanamori et al (1994), 3.7 and 4.3 mHz, after the 1991 Pinatubo eruption, and 3.8 and 5.1 mHz after the 1982 El Chichón eruption. Again they agree with the frequencies determined by Dautermann, Calais, Lognonné, and Mattioli (2009), who found disturbances with peaks of 1 and 4 mHz (gravity and acoustic waves components); with Nakashima et al (2016), peaks of 3.7 and 4.8 mHz; and with Shestakov et al (2021), peaks of 3.7 and 6.7 mHz. Other cases for major earthquakes are those reported by Choosakul et al (2009) observed after the 26 December 2004 Sumatra-Andaman earthquake (Mw 9.3), and Rolland et al (2011) andSaito et al (2011) after the 11 March 2011 Tohoku-oki earthquake (Mw 9.0).…”
Section: Covolcanic Disturbances and Resonancesupporting
confidence: 89%
See 2 more Smart Citations
“…These periodicities also agree with the atmospheric oscillations found by Kanamori et al (1994), 3.7 and 4.3 mHz, after the 1991 Pinatubo eruption, and 3.8 and 5.1 mHz after the 1982 El Chichón eruption. Again they agree with the frequencies determined by Dautermann, Calais, Lognonné, and Mattioli (2009), who found disturbances with peaks of 1 and 4 mHz (gravity and acoustic waves components); with Nakashima et al (2016), peaks of 3.7 and 4.8 mHz; and with Shestakov et al (2021), peaks of 3.7 and 6.7 mHz. Other cases for major earthquakes are those reported by Choosakul et al (2009) observed after the 26 December 2004 Sumatra-Andaman earthquake (Mw 9.3), and Rolland et al (2011) andSaito et al (2011) after the 11 March 2011 Tohoku-oki earthquake (Mw 9.0).…”
Section: Covolcanic Disturbances and Resonancesupporting
confidence: 89%
“…(2016), peaks of 3.7 and 4.8 mHz; and with Shestakov et al. (2021), peaks of 3.7 and 6.7 mHz. Other cases for major earthquakes are those reported by Choosakul et al.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The atmospheric and seismic signals created by volcanic eruptions have been examined extensively and many have documented the acoustic and gravity modes dominant in different data inquiries related to various eruptions (Mauk, 1982;Ripepe, et al, 2016;De Angelis et al, 2011;Kanamori & Watada, 1992;Yue et al, 2022;Shestakov, et al, 2021). Progresses in observational capabilities, primarily advances in GNSS infrastructure, have allowed for a variety of Covolcanic Ionospheric Disturbance(s) (CVIDs) to be detected and the subsequent analysis shows promise for using relative CVID magnitudes as indicators for various source parameters, such as energy estimation, ground peak velocity and plume height (Manta, et al, 2021;Dautermann et al, 2009;).…”
Section: Introductionmentioning
confidence: 99%
“…Volcanic eruptions can produce gravity, acoustic‐gravity, and acoustic waves that can perturb the ionosphere, generating the so‐called co‐volcanic ionospheric disturbances (CVIDs) (Aa et al., 2022; Astafyeva, 2019; Dautermann et al., 2009; Heki, 2006; Manta et al., 2021; Meng et al., 2019; Shestakov et al., 2021; Shults et al., 2016). The HTHH eruption generated a variety of atmospheric waves detected all over the world (Matoza et al., 2022; Themens et al., 2022).…”
Section: Introductionmentioning
confidence: 99%